Erosive and buffering capacities of yogurt - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2007)
Objective: The capability of drinks and foods to resist pH changes brought about by salivary buffering may play an important role in the erosion of dental enamel. The aim of the present study was to measure the initial pH of several types of yogurt and to test the degrees of saturation (pK-pl) with respect to hydroxyapatite and fluorapatite to determine the buffering capacity and related erosive potential Of yogurt. Method and Materials: Twenty-five milliliters of 7 types of freshly opened yogurt was titrated with 1 mol/L of sodium hydroxide, added in 0.5 mL increments, until the pH reached 10, to assess the total titratable acidity, a measure of the drink's own buffering capacity. The degrees of saturation (pK-pl) with respect to hydroxyapatite and fluorapatite were also calculated, using a computer program developed for this purpose. For statistical analysis, samples were compared using Kruskal-Wallis test. Results: The buffering capacities can be ordered as follows: fruit yogurt > low-fat yogurt > bioyogurt > butter yogurt > natural yogurt > light fruit yogurt > light yogurt. The results suggest that, in vitro, fruit yogurt has the greatest buffering capacity. Conclusion: It can be stated that it is not possible to induce erosion on enamel with any type of yogurt.
Keywords: buffering capacity; dental erosion; fluorapatite; hydroxyapatite; yogurt; DENTAL EROSION; SOLUBILITY; DRINKS